Theophylline in patients with syncope without prodrome, normal heart, and normal electrocardiogram: a propensity-score matched study verified by implantable cardiac monitor. Issue 7 (29th November 2021) - Brignole, Michele; Iori, Matteo; Strano, Stefano; Tomaino, Marco; Rivasi, Giulia; Ungar, Andrea; Carretta, Domenico; Solari, Diana; Napoli, Paola; Deharo, Jean Claude; Guieu, Regis
Abstract: Aims: Syncope without prodromes in subjects with normal heart and normal electrocardiogram (ECG) is classified as non-classical neurally mediated syncope and is characterized by low adenosine plasma levels (APLs) and frequent asystolic syncope. We assessed the efficacy of theophylline, a non-selective adenosine receptor antagonist, in preventing syncopal events. Methods and results: Participants received an implantable cardiac monitor, underwent APL measurement, and received oral theophylline at maximum tolerated dose (starting dose 300 mg b.i.d.). They were compared with a historical cohort of untreated patients with implantable cardiac monitor who had the same inclusion criteria and were balanced with the propensity score (PS) method as regard age, sex, lifetime syncopal episodes, APL, and antihypertensive drugs. Primary endpoint was time to first syncopal recurrence at 24 months. There were 76 patients in the theophylline group and 58 in the control group. Syncope recurred in 25 (33%) patients in the theophylline group and in 27 (47%) patients in the control group, with an estimated 2-year recurrence rate of 33% and 60%, respectively, and a hazard ratio of 0.53 [95% confidence interval (CI), 0.30–0.95; P = 0.034]. Most of the benefit of theophylline is derived from reduction of syncope due to asystolic atrioventricular (AV) block (hazard ratio of 0.13; 95% CI, 0.03–0.58; P = 0.008). Thirty (39%) patients discontinued theophylline after a median of 6.4 (interquartile range 1.7–13.8) months due to side effects. Conclusion: Theophylline was effective in preventing recurrences in patients with syncope without prodromes, normal heart, and normal ECG. The benefit was greater in patients with syncope due to asystolic AV block. ClinicalTrials.gov Identifier: NCT03803215.